2021
DOI: 10.18087/cardio.2021.1.n1331
|View full text |Cite
|
Sign up to set email alerts
|

Factors of Progression and Occurrence of Atherosclerosis in Rheumatoid Arthritis

Abstract: Aim      To determine in a prospective study factors of progressive atherosclerotic lesion of blood vessels in patients with rheumatoid arthritis (RA).Material and methods  This prospective study included 124 patients with RA and suspected ischemic heart disease (IHD) and 30 patients with IHD (comparison group) aged 58 [52; 63] years. On enrollment to the study and at 3 years of follow-up, all patients underwent clinical and instrumental examination according to European and Russian guidelines for diagnosis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
0
2
0
1
Order By: Relevance
“…It has been shown that chronic systemic inflammation plays an important role in accelerated atherogenesis in autoimmune diseases. Inflammation can have a direct impact on the development of atherosclerosis or indirectly enhance the effect of traditional cardiovascular risk factors [ 14 , 31 , 32 ]. One of the mechanisms of the atherosclerotic process connecting inflammation and atherothrombosis is the activation of the CD40/CD40L signaling system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that chronic systemic inflammation plays an important role in accelerated atherogenesis in autoimmune diseases. Inflammation can have a direct impact on the development of atherosclerosis or indirectly enhance the effect of traditional cardiovascular risk factors [ 14 , 31 , 32 ]. One of the mechanisms of the atherosclerotic process connecting inflammation and atherothrombosis is the activation of the CD40/CD40L signaling system.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the progression of the immunopathological process in RA is accompanied by the development of a wide range of immunoinflammatory reactions, which may have pathophysiological significance in the development of atherosclerosis. The imbalance of cytokines and the accumulation of inflammatory mediators contribute to the development of vascular disorders associated with atherogenesis—endothelial dysfunction, vasoconstriction, lipid and lipoprotein peroxidation, hypercoagulation—and later lead to the formation and destabilization of atherosclerotic plaques and the development of cardiovascular complications [ 13 , 14 ]. It was shown that in the assessment of early atherosclerotic vascular changes, the prognostic significance of soluble CD40 ligand (sCD40L) and adhesion molecules—intercellular adhesion molecule-1 (sICAM-1) and vascular cell adhesion molecule-1 (sVCAM-1)—was significantly higher compared to other biological mediators [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Фомичева и соавт. [44] в течение 3 лет наблюдали 124 больных РА с подозрением на ишемическую болезнь сердца (ИБС). На момент включения в исследование атеросклеротические бляшки в сонных артериях были выявлены в 77% случаев, атеросклеротическое поражение коронарных артерий -в 7%.…”
unclassified